Dermal Tattoo Biosensors for Colorimetric Metabolite Detection. (3rd July 2019) - Yetisen, Ali K.; Moreddu, Rosalia; Seifi, Sarah; Jiang, Nan; Vega, Katia; Dong, Xingchen; Dong, Jie; Butt, Haider; Jakobi, Martin; Elsner, Martin; Koch, Alexander W.
Abstract: Tattooing is a ubiquitous body modification involving the injection of ink and/or dye pigments into the dermis. Biosensors in the form of tattoos can be used to monitor metabolites in interstitial fluid. Here, minimally invasive, injectable dermal biosensors were developed for measuring pH, glucose, and albumin concentrations. The dermal pH sensor was based on methyl red, bromothymol blue, and phenolphthalein, which responded to a pH range from 5.0 to 9.0. The dermal glucose sensor consisted of glucose oxidase, 3, 3′, 5, 5′‐tetramethylbenzidine, and peroxidase that detected concentrations up to 50.0 mmol L −1 . The dermal albumin sensor consisted of 3′, 3′′, 5′, 5′′‐tetrachlorophenol‐3, 4, 5, 6‐tetrabromosulfophthalein to measure concentrations up to 5.0 g L −1 . The sensors were multiplexed in ex vivo skin tissue and quantitative readouts were obtained using a smartphone camera. These sensors can be used to manage of acid–base homeostasis, diabetes, and liver failure in point‐of‐care settings. Abstract : Geht unter die Haut : Kolorimetrische dermale Sensoren in Form von Tätowierungen wurden für die Bestimmung von pH‐Wert, Glucose‐ und Albumin‐Konzentrationen in einem Ex‐vivo‐Schweinhaut‐Gewebemodell entwickelt. Die Sensoren wurden in einem Array‐Format zur parallelen Detektion in die Dermis injiziert. Eine quantitative Auslesung erfolgte mit einer Smartphone‐Kamera.